Comprehensive quantification of purine and pyrimidine metabolism in Alzheimer's disease postmortem cerebrospinal fluid by LC–MS/MS with metal‐free column. (7th January 2020) - Muguruma, Yoshio; Tsutsui, Haruhito; Akatsu, Hiroyasu; Inoue, Koichi
Abstract: The metabolome presence of nucleobases, nucleosides, nucleotides and related phosphorylated metabolites has been examined for Alzheimer's disease (AD). Although reversed‐phase liquid chromatography tandem mass spectrometry (LC–MS/MS) has been used for the determination of these analytes, they were limited in chromatographic signal intensity and reproducibility owing to significant peak tailing caused by complexing with metallic cations and phosphate groups. In this work, we applied LC–MS/MS analysis with a metal‐free column for comprehensive quantification of 40 analytes regarding to purine and pyrimidine metabolism in postmortem cerebrospinal fluid (pCSF) from AD patients. For the analytical column, an InertSustain AQ‐C18 metal‐free PEEK column was used. MS detection was by electrospray positive ionization. The metal‐free column allowed for sharp peak detection of highly polar metabolites within a running time of 17 min. In validation, the limits of detection (LOD), the limit of quantitation (LOQ) and recovery value using a pooled pCSF sample are 1–500 nM, 0.5–250 nM and a range of 53.1–144.0% (RSD ranged from 0.4 to 19.6%). The developed LC–MS/MS method utilizing a metal‐free column provides an accurate quantification of some metabolites regarding purine and pyrimidine metabolism in pCSF samples obtained from AD patients.